Signa Vitae 2020
DOI: 10.22514/sv.2020.16.0098
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac arrest pharmacotherapy with prefilled syringes improves adherence to Advanced Life Support protocol in understaffed resuscitation pre-hospital care teams

Abstract: Every procedural facilitation or a change in available equipment in treatment of out-of-hospital arrest (OHCA) by two-person teams may significantly enhance their performance quality. The aim of this study was to assess the impact of adrenaline in prefilled syringes on improving the adherence to Advanced Life Support protocol by understaffed teams. The research was based on a randomized cross-over high-fidelity simulation study. Two-person teams took part in two 10-minute simulation scenarios featuring sudden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Three simulation studies in two-member ALS teams focused on the effect of using pre-filled syringes with medication. 27 , 28 , 29 All three studies reported reduced time to adrenaline administration 27 , 28 , 29 , while two noted a shorter time to intravenous or intraosseous access. 27 , 29 One study found a higher chest compression fraction and quicker airway management.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Three simulation studies in two-member ALS teams focused on the effect of using pre-filled syringes with medication. 27 , 28 , 29 All three studies reported reduced time to adrenaline administration 27 , 28 , 29 , while two noted a shorter time to intravenous or intraosseous access. 27 , 29 One study found a higher chest compression fraction and quicker airway management.…”
Section: Resultsmentioning
confidence: 96%
“…Time to airway securing The use of multifunction pads: improved CC quality, earlier airway securing. Zalewski (2020C) 29 Paramedics ( n = 106) ALS/CPR with pre-filled medication syringes Time to critical interventions, CC quality measures The use of pre-filled syringes with adrenaline and amiodarone: faster achievement of critical interventions, CC quality did not differ. Legend.…”
Section: Resultsmentioning
confidence: 99%